REVISION OF HISTORIOGRAPHY OF THE REPUBLICAN INSURGENTS: NICOLAS BRAVO, JUAN ALVAREZ AND VICENTE GUERRERO (Tzintzun, Revista de Estudios Históricos, 2016)
In this work we examine the production of historiography which has beenrealized on three distinguished personages of the south of Mexico (presentstate of Guerrero) personages who participated military and politically inthe independence and republican processes. Not only the historical workthat describes them is quantified, but there is also a valuation of its reachesand their real contribution. It is presented the imbalance of the productionas far as amount and condition, trying for identifying the intellectualyearnings that originated it. The article defines that the thickness of thisproduction maintains the same methodological and appreciative support.
Keywords: biographies; revision of historiography; insurgents; republicans